2005
DOI: 10.1177/0731684405054333
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Finite Element Analysis of Thermomechanical Behavior in Flip-chip Packages under Temperature Cycling Conditions

Abstract: Flip-chip packaging provides a high-performance low-cost approach for the development of electronic packages. A three-dimensional viscoelastic-plastic finite element analysis using the commercial software ANSYS has been performed to study the thermomechanical behavior in flip-chip assemblies, i.e., the four components, chip, solder ball, underfill, and substrate. The viscoelastic behavior of the underfill is modeled on the Maxwell constitutive equation while the viscoplastic behavior of the solder balls is mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This under fill then acts as a thermal stress absorber around the solder balls, thereby reducing stress on the solder joints and improving fatigue life. The problem with this is that they most under fill materials have a tendency to absorb moisture the problem with this is that most under fill materials have a tendency to absorb moisture during preconditioning/storage [4]. Thermal Stresses are induced in electronic packages during various stages of their lifecycle.…”
Section: Literature Survey On Flip Chip Ball Grid Arraymentioning
confidence: 99%
“…This under fill then acts as a thermal stress absorber around the solder balls, thereby reducing stress on the solder joints and improving fatigue life. The problem with this is that they most under fill materials have a tendency to absorb moisture the problem with this is that most under fill materials have a tendency to absorb moisture during preconditioning/storage [4]. Thermal Stresses are induced in electronic packages during various stages of their lifecycle.…”
Section: Literature Survey On Flip Chip Ball Grid Arraymentioning
confidence: 99%
“…Various thermal enhancements have been developed for the basic FC-PBGA package to improve thermal performance. Gugliermermetti and Grignaffini [2] analyzed theoretically the thermal performance of parallel stacks of in-line plate fin heat sinks. They reported that a fin efficiency parameter, like that used for constant cross-section fin in an isothermal fluid flow, can be introduced to express both the local and overall heat transfer balances.…”
Section: Introductionmentioning
confidence: 99%